Meson wave function from holographic models; Physical Review D; Vol. 80, iss. 5 - Vega A. Alfredo; Schmidt I. Ivan; Lyubovitskiy (Lyubovitskij) V. E. Valery Efimovich; Branz T. Tanja; Gutsche Th. Thomas (2009, 2009)
Title screen